Role of Citric Acid Modification on Hydrodesulfurization of DBT and 4,6 DMDBT in the Presence of Pyridine Over CoMo/Al2O3 - Pawinee Sintarako; Piyasan Praserthdam; Vivan Thammongkol; Banpot Pokacharoenwatjana; Watchara Yuanglamyai; Chattrapha Inthiwong (ASEAN Journal of Chemical Engineering, 2015)
In this study, the effect of pyridine as a basic nitrogen compound on HDS activity of DBT and 4,6 DMDBT in treated diesel over modified CoMo/Al2O3 by citric acid has been investigated. It has been obviously found that the modification of CoMo/Al2O3 catalyst by citric acid can inhibit the influence of pyridine on HDS activity of DBT and 4,6 DMDBT. This can be explained that when citric acid was applied in the catalyst preparation, the increasing of total amount of acid sites and the enhancement of HDN activity play an important role in the tolerance of pyridine.